Tacrolimus rescue therapy in resistant or relapsing cases of primary glomerulonephritis - (:unkn) unknown (WICHTIG EDITORE, 2008)
Background: Patients with resistant or relapsing primary glomerulonephritis (PGN) after conventional immunosuppressive treatment have a worse renal outcome, and treatment of these patients remains problematic. In this study we aimed to determine the effect of tacrolimus in these patients. Methods: We prospectively studied 15 patients with PGN (3 membranous nephropathy, 6 membranoproliferative GN, 4 focal segmental glomerulosclerosis [FSGS], 1 IgA nephropathy and 1 IgM nephropathy) who were either resistant (n=7) or relapsing (n=8) after or during conventional immunosuppressive therapy. Tacrolimus was started at a dosage of 0.05 mg/kg per day. Prednisolone was either maintained or added to the tacrolimus regimen. Results: The mean duration of tacrolimus treatment was 28.9 +/- 2.4 months. Proteinuria decreased from 6.3 +/- 5.0 g/day to 0.5 +/- 0.6 g/day at the end of follow-up (p=0.001). Complete or partial remission was achieved by 60% and 40% of patients, respectively. Relapse occurred in only 2 patients with FSGS under tacrolimus treatment. There was no significant change in serum creatinine at the end of follow-up (from 1.4 +/- 1.0 mg/dL to 1.2 +/- 0.6 mg/dL, p=0.3). Serum albumin increased from 3.2 +/- 0.5 g/dL to 4.3 +/- 0.3 g/dL (p=0.0001). There were 6 relapses among 10 patients after the withdrawal of tacrolimus. Conclusions: These data suggest that the combined therapy of tacrolimus and low-dose prednisolone may have a promising role to obtain long-term remission in resistant or relapsing PGN.
Keywords: Primary glomerulonephritis; Proteinuria; Tacrolimus; FOCAL SEGMENTAL GLOMERULOSCLEROSIS; MEMBRANOUS NEPHROPATHY; NEPHROTIC SYNDROME; CYCLOSPORINE-A; RANDOMIZED-TRIAL; CHILDREN; DISEASE; ADULTS